1964
DOI: 10.1038/icb.1964.64
|View full text |Cite
|
Sign up to set email alerts
|

Stop‐flow Analysis of Renal Tubular Function in the Rat Undergoing Osmotic Diuresis Due to Creatinine Loading

Abstract: Summary 1. A brisk osmotic diuresis was produced in rats by the intravenous infusion of 8 per cent creatinine in Ringer's solution at 0·39 ml./minute. Steady‐state conditions were attained after 25 minutes of infusion. During the period of infusion between 25–43 minutes, six urine and three plasma samples were collected in each of a series of seven animals, and the creatinine clearance and urinary excretion of water, creatinine, sodium and potassium were found to be constant. Mean values and standard deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The curves for sodium, PAH, and creatinine are similar to those reported previously in rats [17][18][19]. Magnesium exhibits a distal dip in the same region as sodium.…”
Section: Resultssupporting
confidence: 75%
“…The curves for sodium, PAH, and creatinine are similar to those reported previously in rats [17][18][19]. Magnesium exhibits a distal dip in the same region as sodium.…”
Section: Resultssupporting
confidence: 75%
“…Failure of previous workers to demonstrate creatinine secretion on stop flow in the rat could be due to differences in technique. Young & Edwards (1964) used creatinine as the diuretic agent and so their rats had extremely high plasma levels of creatinine. It is likely that this fact served to mask any secretion which may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…ALICE M. HARVEY AND RICHARD L. MALVIN flow has been used extensively in the dog but far less frequently in the rat (Williamson, Skulan & Shideman, 1961;Young & Edwards, 1964). We have shown that the clearance ratio of creatinine to inulin in the male rat exceeds unity, indicating creatinine secretion in this animal (Harvey & Malvin, 1965).…”
mentioning
confidence: 83%
See 2 more Smart Citations